Attitude and motivation towards a working language: case of East Timorese students in the Philippines - Edward Jay Mansarate Quinto, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This study explores the attitude and motivation of ten East Timorese students in the Philippines towards English, one of East Timor’s two working languages. Five themes corresponding to the research questions emerged from the semi-structured interviews conducted in this qualitative study: (1) English as a favored language, (2) English as an indicator of competence, (3) English as a vehicle for communication, (4) English as an edge in the workplace, and (5) English as a global/international status marker. Results point to the participants’ favorable attitude toward English because of its value as a linguistic tool, an instrument in the achievement of personal and career goals, and a utilitarian language. Based on a proposed four-fold typology, the researcher found that the participants are driven because of their favorable attitude and instrumental motivation toward English. The results challenge EFL teachers to consider the difference between English taught as a foreign language and English learned as a foreign language, as the former is conservative and to a certain extent prescriptivist, whereas the latter takes into account the attitudinal and motivational aspects of language learning which are a necessary component of any successful learning of a language.